2012
DOI: 10.3136/fstr.18.333
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Flow Rate on Subcritical-water Extraction from Defatted Rice Bran

Abstract: The effect of the subcritical water treatment along with the combination of static and dynamic modes on the recovery of protein, carbohydrate and phenolic substances from defatted rice bran was investigated at various treatment temperatures of 120, 160, 200 and 250℃ and the flow rates of 0.5, 2.5 and 5 mL/ min. The highest amounts of protein and carbohydrate were recovered at 160℃ and that of the phenolic substances was recovered at 250℃. Around half of the protein and carbohydrate contents were degraded at 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In brief, low temperature, longer extraction time, and low biomass loading during SWE support high carbohydrate yields. Extraction of carbohydrate gives negative effects because carbohydrate rapidly decomposed when exposed to higher temperatures [30, 31]. Also, biomass loading has an effect on carbohydrate extraction as the yield decreases when the sample is concentrated.…”
Section: Resultsmentioning
confidence: 99%
“…In brief, low temperature, longer extraction time, and low biomass loading during SWE support high carbohydrate yields. Extraction of carbohydrate gives negative effects because carbohydrate rapidly decomposed when exposed to higher temperatures [30, 31]. Also, biomass loading has an effect on carbohydrate extraction as the yield decreases when the sample is concentrated.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, several studies have shown that subcritical water, that is water in the temperature range of 100–374°C under pressure that is high enough to keep it in liquid state, can be used as an extractant for various groups of compounds . The extraction of phenolic compounds from agricultural materials is one of the applications of subcritical water . Some advantages of subcritical water extraction over others conventional organic solvent extraction methods have been demonstrated in these studies, for example it is an environmentally friendly method and has a high efficiency for the extraction of phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The extraction of phenolic compounds from agricultural materials is one of the applications of subcritical water. [4][5][6][7] Some advantages of subcritical water extraction over others conventional organic solvent extraction methods have been demonstrated in these studies, for example it is an environmentally friendly method and has a high efficiency for the extraction of phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…120) Static and dynamic modes have also been tested at various treatment temperatures and flow rates in a packed column in order to determine the effect on protein, carbohydrate, and phenolic recovery. 121) Additional extracts were prepared after 5 min of treatment at 230°C in water and 40% (v/v) acetone, after which those substances soluble in acetone were fractionated from both. The antioxidative activities of the extracts and fractions were then tested against DPPH, hydroxyl and peroxyl radicals, and hypochlorite and peroxynitrile ions and were characterized using a 5-axe cobweb chart.…”
Section: Reactions In Subcritical Watermentioning
confidence: 99%